Effects of androgen deprivation therapy on cognitive functions in patients with metastatic prostate cancer: A multicentric, prospective study of the Society of Urological Surgery Andrology group. Issue 6 (28th February 2021) - Cinar, Onder; Turunc, Tahsin; Kazaz, Ilke Onur; Yildirim, Omer; Deliktas, Hasan; Cihan, Ahmet; Gudeloglu, Ahmet; Ure, Iyimser; Deveci, Serkan; Sahin, Bahadir; Cinar, Bilge Piri; Ozkara, Hamdi
Abstract: Aims of the study: The aim of this study was to investigate the impact of testosterone deficiency on cognitive functions in metastatic prostate cancer patients receiving androgen deprivation therapy (ADT). Methods: In this multicentric prospective study, 65 metastatic prostate cancer patients were evaluated. Demographic and clinical data were recorded. Cognitive functions were assessed using the Symbol Digit Modalities Test, the California Verbal Learning Test Second Edition, the Brief Visuospatial Memory Test—Revised, and the Trail Making Test. Depressive symptoms were assessed using the Beck Depression Inventory. Cognitive functions and depressive symptoms were recorded before the androgen deprivation therapy and at the 3‐ and 6‐month follow‐ups. Results: At the basal cognitive assessment, the mean Symbol Digit Modalities Test, the California Verbal Learning Test Second Edition, the Brief Visuospatial Memory Test—Revised scores were 25.84 ± 17.54, 32.68 ± 10.60, and 17.63 ± 11.23, respectively, and the mean time for the Trail Making Test was 221.56 ± 92.44 seconds, and were similar at the 3‐month, and 6‐month controls ( P  > .05). The mean pretreatment, third and sixth month testosterone levels were 381.40 ± 157.53 ng/dL, 21.61 ± 9.09 ng/dL and 12.25 ± 6.45 ng/dL ( P  < .05), and the total PSA levels were 46.46 ± 37.83 ng/mL, 1.41 ± 3.31 ng/mL and 0.08 ± 0.14 ng/mL ( P  < .05), respectively. Conclusion: The ADT in patients with metastatic prostate cancer does not affect patients' cognitive functions and depressive symptoms. However, further prospective randomised studies with higher cohorts and longer follow‐up periods are needed.